PENGEMBANGAN LKPD BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI SEKOLAH DASAR MATERI PERUBAHAN WUJUD BENDA - Rani Octaviani; Nirwana Anas; Ramadan Lubis (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Critical thinking is very important for every individual in facing various problems in everyday life in order to solve their own problems. Data collection methods in this study include observation, questionnaires, and tests, the tests here include the initial test (pre-test) and the final test (post-test). The level of validity of STEM-based LKPD on the material of changes in the form of objects is said to be very valid, according to the results of the assessment of three experts, namely material experts, namely 84% (very valid), media experts, namely 87.5% (very valid), and class teachers at MIN 7 Medan by 86.3% (very valid). The level of practicality of STEM-based LKPD to improve critical thinking skills on the material of changes in the form of objects is categorized as practical, according to the results of small-scale trials with a percentage of 89.2% with a very practical category, and large-scale trials with a percentage of 91.0% with a very practical category. The level of effectiveness of STEM-based LKPD on the material of changes in the form of objects with an N-Gain score scale assessment is categorized as high, namely 0.73 and is categorized as high to improve critical thinking skills in students with a post-test score of 83.6%. From all the results above, it can be concluded that STEM-based LKPD can improve critical thinking skills in elementary schools, and is suitable for use in the school environment.